Influence Of Leadership And Motivation On Employee Performance With Organizational Culture As A Mediating Variable Case Study Of Employees At Pt. Warga Utama Prima Mandiri - Noviyanti, Reza; Padmakusumah, Rizal Ramdan (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the influence of leadership and motivation on employee performance with organizational culture as a mediating variable. This study was conducted at PT Warga Utama Prima Mandiri located in Purwakarta City, West Java. The population in this study were all 142 employees of PT Warga Utama Prima Mandiri, with a sample of 105 people using the Slovin formula. A quantitative approach was used with data collection through distributing questionnaires, which were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results of the study showed that organizational culture had a significant effect on employee performance. The better the organizational culture created, the higher the employee performance. Leadership had a significant effect on employee performance. Organizational culture was proven to mediate the influence of leadership on employee performance. This means that leaders not only have a direct impact, but also strengthen performance. Organizational culture also mediates the relationship between work motivation and employee performance. High motivation in employees will have an optimal effect if accompanied by a supportive organizational culture.